Effects of limited knee flexion movement in intra-limb gait coordination - Celestino, M. L.; van Emmerik, R.; Barela, J. A.; Bacca, O.; Barela, A. M. (Journal of Biomechanics, 2021)
This study aimed to investigate intra-limb coordination in non-disabled individuals walking with and without a constrained knee and in individuals with stroke. We hypothesized that a constrained knee would modify the intra-limb coordination of non-disabled individuals and that non-disabled individuals walking with a constrained knee would present coordination patterns similar to those presented by individuals with stroke. Twelve individuals with chronic stroke (age: 54.1 ± 9.9 years) and 12 age- and sex-matched individuals (age: 54.8 ± 9.2 years) with no known gait impairment (non-disabled individuals) participated in this study. Non-disabled individuals walked with and without an orthosis on one of their knees, limiting flexion to 40°, which was the average maximum knee flexion presented by the participants with stroke. Lower limb coordination was assessed on the basis of vector coding for the thigh-shank and shank-foot couplings during stance and swing periods of gait. Constrained knee flexion in non-disabled individuals mainly affected the thigh-shank coupling but not the shank-foot coupling of the constrained limb. There was reduced anti-phase coordination during the stance and swing periods and a marked increase in in-phase coordination during the swing period. Non-disabled individuals presented most changes toward the coordination pattern presented by individuals with stroke, except for the thigh-phase mode during the swing period, which was lower than that in individuals with stroke. Reduced knee flexion movement caused similar alterations in the intra-limb coordination pattern in non-disabled individuals compared to those observed in individuals with stroke. Therefore, diminished knee flexion movement, which is presented by individuals with stroke, can be considered a key disturbance that leads to impairment in lower extremity intra-limb coordination.